2013
DOI: 10.1002/cbic.201200733
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Access Tunnels and Active‐Site Cavities Influence Activity of Haloalkane Dehalogenases in Organic Cosolvents

Abstract: The use of enzymes for biocatalysis can be significantly enhanced by using organic cosolvents in the reaction mixtures. Selection of the cosolvent type and concentration range for an enzymatic reaction is challenging and requires extensive empirical testing. An understanding of protein-solvent interaction could provide a theoretical framework for rationalising the selection process. Here, the behaviour of three model enzymes (haloalkane dehalogenases) was investigated in the presence of three representative or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 95 publications
1
35
0
Order By: Relevance
“…Here we focus on these channels, as the active site access paths play an important role in substrate and product trafficking between active site and outside. It has been shown that mutations in enzymes’ active site access channels alter the substrate preferences of haloalkane dehalogenase enzymes and may be utilized in rational design of enzymes [26,27]. The amino acids lining the access channels of cytochrome P450 (CYP) are important for the selectivity of these enzymes [28] while the flexibility of these channels, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Here we focus on these channels, as the active site access paths play an important role in substrate and product trafficking between active site and outside. It has been shown that mutations in enzymes’ active site access channels alter the substrate preferences of haloalkane dehalogenase enzymes and may be utilized in rational design of enzymes [26,27]. The amino acids lining the access channels of cytochrome P450 (CYP) are important for the selectivity of these enzymes [28] while the flexibility of these channels, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Volumes of the FMN binding sites were calculated using an in-house code attached as supplemental material that is based on a procedure described by Stepankova et al [28]. That procedure uses atoms that define the location of the binding site of interest in a snapshot from the MD simulation, and a sphere enclosing the measured space.…”
Section: Calculation Of Fmn Binding Site Volumementioning
confidence: 99%
“…Recent evidence has highlighted the importance of protein flexibility in protein access and egress tunnels [9], [10]. For instance, Stepankova et.…”
Section: Introductionmentioning
confidence: 99%
“…al. demonstrated that at low concentrations organic solvents cause the widening of tunnels in haloalkane dehalogenase enzymes resulting in either increased activity or inhibition depending on the system and the solvent used [10]. Furthermore, in several cytochrome P450 (CYP) enzymes, phenylalanine clusters located in ligand entrance tunnels just above the active site act as gates that must be properly oriented to allow substrate binding [9], [11].…”
Section: Introductionmentioning
confidence: 99%